負荷様式による等尺性収縮筋力の違い - 田路, 秀樹; 比嘉, 昌 (Transactions of Japanese Society for Medical and Biological Engineering, 2016)
It is well known that maximum voluntary torque, produced by skeletal muscles is lower during concentric contraction and higher during eccentric contraction compared with isometric contraction. The steady state property defined by its isometric strength is commonly used. We focus on isometric contraction in detail. The purpose of this study is to measure maximum isometric strength both at active and passive conditions and to examine the condition-related contribution of neural and force mechanics to the force. Six healthy subjects participated in this study. The strength of their elbow flexors and electromyogram (EMG) were measured during the two conditions. As results, the passive condition led to stronger force in maximal isometric significantly while EMG did not show significant changes. In other words, we can sustain stronger force enduring external forces rather than exerting one's maximal voluntary forces against a fixed object.